Fenomena Tumbler Tuku Di Kai Dalam Perspektif Cyber Pragmatik - Mika Charolin; Intan Valiza; Mesya Fadila Sani Harahap; Muhammad Ridho Afarrel; Afriani Sasmita Br Manurung; Oky Fardian Gafari; Herning Puspitarini (CV. SINAR HOWUHOWU, 2026)
The viral phenomenon of